Chemo‐enzymatic three‐fragment assembly of semisynthetic proteins‡. (9th January 2014) - Schmohl, Lena; Schwarzer, Dirk; Becker, Christian
<x xml:space="preserve">Abstract</x> Here, we report the development of a method for three‐fragment assemblies of semisynthetic proteins by combining sortase‐mediated ligation with site‐specific bioconjugation catalyzed by the 4′‐phosphopantetheine transferase Sfp. This method enables the introduction of synthetic peptides into central regions of proteins without the need to purify intermediates. The assembled proteins are linked at the N‐terminal junction with a 4′‐phosphopantetheine moiety and with a peptide bond at the C‐terminal ligation site. We have demonstrated the applicability of this method by assembling a semisynthetic model protein derived from fluorescence resonance energy transfer‐based reporters from three fragments in a one‐pot reaction. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.